A comprehensive strategy integrating metabolomics with multiple chemometric for discovery of function related active markers for assessment of foodstuffs: A case of hawthorn (Crataegus cuneata) fruits. (30th July 2022) - Cui, Yan; Du, Kunze; Hou, Shixin; Yang, Rui; Qi, Lina; Li, Jin; Chang, Yanxu
Highlights: Integrated metabolomics with chemometrics were used to screen bioactive markers. Seven compounds with antithrombin activity were identified in hawthorn fruits. The function-related active markers were discovered for assessment of foodstuffs. Abstract: There is a growing demand for functional foodstuffs naturally rich in nutrients and bioactive compounds associated with putative health benefits. This study followed a strategy integrating metabolomic with chemometric to identify quality markers that can be used to distinguish function related bioactivity of fruits, using hawthorn (Crataegus cuneata) fruit as an example. The integrated strategy was reduced to characterization of metabolic processes and discovered potential bioactive ingredients that were further investigated for functionalities. This comprehensive process provided guidance for discovery of function-related active markers for assessment of foodstuffs.